Revitalizing Pandan Mat MSMEs: A Journey of Product Diversification in Kadumaneuh, Pandeglang Regency - Suyana, Hilma; Hayurani, Herika; Rofi’i, Muhammad (Entrepreneurship and Community Development, 2025)
This community service aims to increase the added value of pandan mat Micro, Small and Medium Enterprises (MSME) products in Kadumaneuh Village, Pandeglang Regency, through product diversification. Pandan mats are local products that have high economic potential but still face challenges in terms of marketing and product innovation. This community service is carried out by involving training for local craftsmen on product diversification techniques, marketing, and effective branding development. The results of this service are expected to increase the knowledge and skills of craftsmen in creating new, innovative products, such as accessories and decorations made from pandan mats. In addition, improving product quality and appropriate marketing strategies are expected to expand market reach and increase MSME income. The resulting managerial implications include the need to improve MSME managerial skills in product design management, the use of digital technology for marketing, and the development of collaborative strategies with other parties to increase production and distribution efficiency. This paper contributes to providing a strategic understanding of the importance of the role of digital marketing and financial literacy as a solution to increase the competitiveness and turnover of MSMEs in the era of digital transformation through a training approach based on partner needs.